“Green Marketing of Durable Products: A Study in Vellore.” - K. Arul; R. Murugan (The Bioscan, 2026)
Green marketing has emerged as an important approach for promoting environmentally friendly products and encouraging sustainable consumption. This study examines the marketing of green durable products with special reference to green marketing practices in Vellore District. The main objective of the study is to analyse consumer awareness, purchase behaviour, satisfaction levels, and factors influencing the adoption of green durable products such as energy-efficient appliances, electric vehicles, and solar- based products.